2014
DOI: 10.1158/0008-5472.can-13-1196
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Hypoxia Does Not Drive Differentiation of Tumor-Associated Macrophages but Rather Fine-Tunes the M2-like Macrophage Population

Abstract: Tumor-associated macrophages (TAM) are exposed to multiple microenvironmental cues in tumors, which collaborate to endow these cells with protumoral activities. Hypoxia, caused by an imbalance in oxygen supply and demand because of a poorly organized vasculature, is often a prominent feature in solid tumors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
294
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 360 publications
(309 citation statements)
references
References 20 publications
12
294
2
1
Order By: Relevance
“…TAMs with low MHC-II expression (MHC-II lo ) populate hypoxic areas, whereas TAMs with high MHC-II expression (MHC-II hi ) populate normoxic areas. While hypoxia does not seem to influence differentiation of these two TAM subsets or MHC-II expression levels, hypoxia does influence the MHC-II lo macrophage phenotype by fine-tuning hypoxia-responsive genes that are involved in metabolism, angiogenesis, and metastasis, thereby fostering tumor progression (74). The underlying mechanism for this phenotypic switch in MHC-II lo compared to MHC-II hi macrophages, as well as why MHC-II lo macrophages specifically reside in hypoxic areas, remains an open question; nevertheless, the gene expression profile specifically affected in these macrophages by hypoxia, such as increased availability of VEGFA, lactate dehydrogenase A (LDHA), or urokinase-type plasminogen activator receptor (uPAR) underscores the contribution of MHC-II lo macrophages to tumor progression.…”
Section: Cd25mentioning
confidence: 93%
“…TAMs with low MHC-II expression (MHC-II lo ) populate hypoxic areas, whereas TAMs with high MHC-II expression (MHC-II hi ) populate normoxic areas. While hypoxia does not seem to influence differentiation of these two TAM subsets or MHC-II expression levels, hypoxia does influence the MHC-II lo macrophage phenotype by fine-tuning hypoxia-responsive genes that are involved in metabolism, angiogenesis, and metastasis, thereby fostering tumor progression (74). The underlying mechanism for this phenotypic switch in MHC-II lo compared to MHC-II hi macrophages, as well as why MHC-II lo macrophages specifically reside in hypoxic areas, remains an open question; nevertheless, the gene expression profile specifically affected in these macrophages by hypoxia, such as increased availability of VEGFA, lactate dehydrogenase A (LDHA), or urokinase-type plasminogen activator receptor (uPAR) underscores the contribution of MHC-II lo macrophages to tumor progression.…”
Section: Cd25mentioning
confidence: 93%
“…Tumor promotion has been linked with an accumulation of M2-oriented MHC II low TAMs in lung and breast carcinoma (3,4). Accordingly, MHC II low TAMs were found to reside primarily in less oxygenated zones, express hypoxia-regulated genes, and facilitate the angiogenic switch (5). Interestingly, the macrophage mannose receptor (MMR, CD206), a typical M2 cell surface marker, is upregulated on these tumor-promoting MHC II low TAMs in all tumor models studied (3)(4)(5).…”
mentioning
confidence: 99%
“…Accordingly, MHC II low TAMs were found to reside primarily in less oxygenated zones, express hypoxia-regulated genes, and facilitate the angiogenic switch (5). Interestingly, the macrophage mannose receptor (MMR, CD206), a typical M2 cell surface marker, is upregulated on these tumor-promoting MHC II low TAMs in all tumor models studied (3)(4)(5). The M1/M2 nomenclature has shortcomings, and a better positioning of TAM subsets within the spectrum of macrophage activation states is warranted (6).…”
mentioning
confidence: 99%
“…More work is needed to elucidate the mechanisms by which hypoxia and immune cells establish microenvironments leading to intratumoral heterogeneity. Enhanced imaging techniques have made it clear that distinct subpopulations of hypoxic cells are present in tumors (125)(126)(127), while histopathological and molecular analyses have shown that distinct tumor regions have different inflammatory infiltrates that can be modulated by intratumoral hypoxia (128,129).…”
Section: Hypoxia and Intratumoral Heterogeneitymentioning
confidence: 99%